Reformation im Diskurs. Akademievorlesungen Oktober 2016 - Januar 2017 - Kreuzer, Edwin J. (Hamburger Akademievorträge, 2018)
Martin Luther's Reformation has changed not only theology and church, but the world itself. In a multifaceted process, Luther's ideas and their effects have transformed church and culture, economy and society and paved the way for the modern age. The contributions in the second volume of the "Hamburger Akademievorträge" deal with these developments which are elementary for contemporary life.